2005
DOI: 10.1002/jmv.20488
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of human caliciviruses in hospitalized children with acute gastroenteritis in Blantyre, Malawi

Abstract: The human caliciviruses (HuCVs), including Norovirus and Sapovirus, are recognized causes of acute gastroenteritis in children and adults. A 1-year study was undertaken in Blantyre, Malawi, to examine the prevalence, and genetic diversity, of human caliciviruses (HuCVs) amongst children under 5 years of age hospitalized with acute gastroenteritis. Using the reverse transcription-polymerase chain reaction (RT-PCR), combined with nucleotide sequencing of the RT-PCR products, HuCVs were detected in 34/398 (8.5%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
56
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 29 publications
12
56
3
Order By: Relevance
“…These results are similar to a Malawian study which demonstrated an autumn peak (MarchApril) [9] and a Kenyan study where SaVs were detected all year round [4]. These results are in contrast to studies from the northern hemisphere (Canada, United Kingdom, Denmark and Japan) where SaVs are more frequent during the cold winter season [27].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are similar to a Malawian study which demonstrated an autumn peak (MarchApril) [9] and a Kenyan study where SaVs were detected all year round [4]. These results are in contrast to studies from the northern hemisphere (Canada, United Kingdom, Denmark and Japan) where SaVs are more frequent during the cold winter season [27].…”
Section: Discussionsupporting
confidence: 87%
“…In these studies, SaVs were common during the winter months and in younger children [1]. Sapovirus prevalence has only been described in a few sub-Saharan African countries, including Kenya (5.7% in <14 years) [6], Tanzania (5.7-6.4% in <5 years) [7,8], Malawi (8% in <5 years) [9], South Africa (SA; 4.1-8.4% in all ages) [10,11], Gabon (9.5% in <5 years) [12] and Burkina Faso (18% in <5 years) [13]. These studies utilized molecular methods for SaV detection with an average prevalence of 7.5% (95% CI 3.4%-11.5%) among diarrhoeal cases.…”
Section: Introductionmentioning
confidence: 93%
“…Mixed infections, involving SaVs and other enteric viruses such as RV, AdV and NoV, at frequencies ranging from 17-26% have been reported previously [17,30,33].…”
Section: Discussionmentioning
confidence: 99%
“…In Tunisia, SaVs were reported in paediatric outpatients with gastroenteritis and only GI.1 was identified [15]. Sapoviruses have also been reported in patients hospitalised with gastroenteritis in Tanzania [16] and in Malawi [17]. Genotypic characterisation was not conducted in the Tanzanian study [16] and in Malawi, only GII strains were identified [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation